Compositions, building and road construction material compositions, asphalt mixture compositions, curable compositions, and curing delay methods.
Patent Information
- Application Number
- JP2025060589
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-14
- Estimated Expiration
- 2045-04-01
Smart Images

Figure 2026167161000001 
Figure 2026167161000002 
Figure 2026167161000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to compositions, building and road construction material compositions, asphalt mixture compositions, curable compositions, and curing delay methods. [Background technology]
[0002] Asphalt mixtures used for road paving and other applications are known as mixed materials consisting of crushed stone, sand, stone powder, and asphalt in predetermined proportions, and are sometimes referred to as asphalt mixtures. In recent years, room-temperature application type asphalt mixtures, which can be applied at room temperature at construction sites, have been used, and various types of such room-temperature application type asphalt mixtures are known (see, for example, Patent Document 1).
[0003] The aforementioned room-temperature application type asphalt mixture contains fatty acids and alkaline components as hardening agents. By adding water as a hardening accelerator, the fatty acids and alkaline components undergo a saponification reaction, causing hardening and enabling the development of high strength. Normally, such room-temperature application type asphalt mixtures do not harden unless a hardening accelerator such as water is present, as the saponification reaction will not begin. However, in some cases, the asphalt mixture may harden during storage due to saponification reactions with moisture contained in the mixture or moisture in the air (hereinafter also referred to as "natural hardening"). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2010-248472 [Overview of the project] [Problems that the invention aims to solve]
[0005] There is a need for an asphalt mixture that can prevent the natural hardening of room-temperature applied asphalt mixtures, and that hardens quickly after water is added during actual application, thereby achieving sufficient strength.
[0006] Accordingly, the object of the present invention is to provide a composition that, when added to asphalt mixtures, suppresses the natural hardening of said asphalt mixtures, and allows the saponification reaction to proceed rapidly after water is added, thereby enabling hardening; a building and road material composition containing said composition; an asphalt mixture composition; and a hardening composition. The object of the present invention is also to provide a method for delaying hardening. [Means for solving the problem]
[0007] As a result of diligent research, the inventors of this invention have newly discovered that the following composition exhibits excellent effects, and have completed the present invention.
[0008] In other words, the present invention relates to a composition comprising an acid component and a polyether polyol, The aforementioned acid component contains a fatty acid with 18 carbon atoms in an area ratio of 40% or more of the total acid component as measured by gas chromatography. The present invention relates to a composition in which the content of the polyether polyol is less than 20% by weight relative to the acid component (100% by weight).
[0009] It is preferable that the above acid component is a fatty acid mixture containing two or more fatty acids.
[0010] Preferably, the polyether polyol is a curing retarder.
[0011] Furthermore, the present invention relates to a building and road construction material composition comprising aggregate, an alkaline additive, and the aforementioned composition, as well as an asphalt mixture composition comprising asphalt, an alkaline additive, and the aforementioned composition.
[0012] Furthermore, the present invention relates to a curable composition obtained by adding water to the aforementioned building and road material composition or asphalt mixture composition.
[0013] Furthermore, the present invention relates to a method for delaying the hardening of the building and road material composition or the asphalt mixture composition before the addition of water. [Effects of the Invention]
[0014] The composition of the present invention contains a specific amount of a fatty acid having 18 carbon atoms and a specific amount of a polyether polyol, thereby delaying the hardening of a building / road material composition or asphalt mixture composition before the addition of water, and enabling rapid hardening after the addition of water. [Modes for carrying out the invention]
[0015] 1. Composition The composition of the present invention (hereinafter also referred to as "this composition") contains an acid component and a polyether polyol, The aforementioned acid component contains a fatty acid with 18 carbon atoms in an area ratio of 40% or more of the total acid component as measured by gas chromatography. This invention relates to a composition in which the content of the polyether polyol is less than 20% by weight relative to the acid component (100% by weight). The components included in the composition of the present invention will be described below.
[0016] <Acid component> As for the acid component, in gas chromatography analysis, it is sufficient if the content of C18 fatty acids is 40 area% or more when the total acid component is considered as 100 area%, and there are no particular limitations on other acid components, but it is preferable that it is a fatty acid mixture containing 40 area% or more of C18 fatty acids and fatty acids other than C18 fatty acids (also called "other fatty acids"). It is also preferable that it contains multiple types of C18 fatty acids. Fatty acids with fewer than C18 are undesirable because they become highly water-soluble after the saponification reaction, and fatty acids with 19 or more C19 are undesirable because they become solid at room temperature. Therefore, if fatty acids with fewer than C18 or fatty acids with 19 or more C19 are included, their content is less than 60 area%. Gas chromatography analysis can be performed by the method described in the examples.
[0017] The fatty acid having 18 carbon atoms may be either a saturated fatty acid or an unsaturated fatty acid, and may be either a linear fatty acid or a branched fatty acid, or may be a mixture thereof. Specific examples thereof include stearic acid, isostearic acid, oleic acid, isooleic acid, linoleic acid, linolenic acid, ricinoleic acid, 16-methylheptadecanoic acid, 15-methylheptadecanoic acid, and the like.
[0018] The other fatty acids described above may be either saturated fatty acids or unsaturated fatty acids, may be either linear fatty acids or branched fatty acids, and may be mixtures thereof.
[0019] Examples of the saturated fatty acids include linear saturated fatty acids or branched saturated fatty acids having 1 to 17 carbon atoms and 19 to 30 carbon atoms. Examples of the linear saturated fatty acids include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, behenic acid, cerotic acid, melissic acid and the like. Examples of the branched saturated fatty acids include isobutyric acid, isovaleric acid, pivalic acid and the like.
[0020] Examples of the unsaturated fatty acids include linear unsaturated fatty acids or branched unsaturated fatty acids having 3 to 17 carbon atoms and 19 to 30 carbon atoms. Examples of the linear unsaturated fatty acids include acrylic acid, crotonic acid, heptenoic acid, myristoleic acid, palmitoleic acid, triacontenoic acid and the like. Examples of the branched unsaturated fatty acids include methacrylic acid, isomyristoleic acid and the like.
[0021] As the other fatty acids contained in the fatty acid mixture, fatty acids having 15 to 17 carbon atoms and 19 to 20 carbon atoms are preferable, and fatty acids having 16 to 17 carbon atoms are more preferable.
[0022] The content of 18-carbon fatty acids (total content if multiple types are included) is 40% or more, preferably 45% or more, more preferably 50% or more, even more preferably 60% or more, even more preferably 70% or more, and particularly preferably 80% or more, relative to the total acid component (100% area). Furthermore, the upper limit of the content is not particularly limited and may be 100% (i.e., the acid component may consist only of 18-carbon fatty acids), 95% or 90%.
[0023] As a fatty acid mixture containing 18-carbon fatty acids in an area ratio of 40% or more by gas chromatography, commercially available products can also be used. Examples of commercially available products include the TFA series from Tsukuno Oleochemicals Co., Ltd. and the Lunac series from Kao Corporation. More specifically, examples include SINAR-OL (trade name, manufactured by SINARMAS CEPSA), TFA-125 (trade name, manufactured by Tsukuno Oleochemicals Co., Ltd.), TFA-80MS (trade name, manufactured by Tsukuno Oleochemicals Co., Ltd.), TFA-145WF (manufactured by Tsukuno Oleochemicals Co., Ltd.), Evap Oleo O-185 (manufactured by Evyap), NAS-125 (manufactured by Tsukuno Oleochemicals Co., Ltd.), TFA-IS4 (manufactured by Tsukuno Oleochemicals Co., Ltd.), etc.
[0024] <Polyether polyol> The composition of the present invention contains a polyether polyol. A polyoxyalkylene polyol having an alkylene oxy group is preferred as the polyether polyol. Specifically, examples include ethylene oxide (EO)-modified trimethylolpropane, propylene oxide (PO)-modified trimethylolpropane, tetrahydrofuran-modified trimethylolpropane, EO-modified glycerin, PO-modified glycerin, tetrahydrofuran-modified glycerin, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and polyethylene glycol-propylene glycol copolymers. In the case of copolymers, they may be block copolymers or random copolymers.
[0025] The ratio of oxyethylene (EO) units to oxypropylene (PO) units in the polyethylene glycol-propylene glycol copolymer may be 100 / 0 to 0 / 100, 100 / 0 to 5 / 95, 100 / 0 to 10 / 90, 100 / 0 to 30 / 70, or 100 / 0 to 60 / 40 in molar ratio (EO / PO).
[0026] The number-average molecular weight of the polyether polyol is not particularly limited, but may be between 200 and 10,000, or between 400 and 6,000.
[0027] Commercially available products can also be used as polyether polyols. Examples of commercially available products include Brownon PEG-600 (trade name, polyethylene glycol) and Brownon P-106 (trade name, polyoxyethylene polyoxypropylene glycol (EO / PO=60 / 40)) from Aoki Oil & Fat Industry Co., Ltd., and Sannix PP-200 (trade name, polypropylene glycol) and Sannix TP-400 (trade name, trimethylolpropane-based polyether polyol) from Sanyo Chemical Industries, Ltd., Newpol PE-61 (trade name, polyoxyethylene polyoxypropylene glycol (EO / PO=12.5 / 87.5)), Newpol PE-71 (trade name, polyoxyethylene polyoxypropylene glycol (EO / PO=9.1 / 90.9)), and Newpol PE-75 (trade name, polyoxyethylene polyoxypropylene glycol (EO / PO=42.9 / 57.1)) from Sanyo Chemical Industries, Ltd.
[0028] The polyether polyol content is less than 20% by weight, preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 1% by weight or less, based on 100% by weight of the total acid component. If the polyether polyol content exceeds 20% by weight, the product may not harden sufficiently after hydration, resulting in a decrease in the strength of the final cured product. By setting the polyether polyol content within the above range, a sufficient hardening delay effect can be obtained, and hardening after hydration can be performed quickly, resulting in a very excellent effect. Furthermore, although there is no particular lower limit, it is preferable to have a value of 0.01% by weight or more from the viewpoint of hardening delay effect.
[0029] The composition of the present invention can be used as a hardening retarder, a heat stabilizer, etc., and more specifically, it can be added as a hardening retarder to building and road material compositions and asphalt mixture compositions. The composition of the present invention has the excellent effect of delaying the natural hardening (hardening before water addition) of building and road material compositions and asphalt mixture compositions, while enabling rapid hardening after water addition. Furthermore, because heat resistance and thermal stability are improved, the loss of volatile fatty acid components when mixed with high-temperature asphalt is reduced, and oxidative degradation due to heat is suppressed, contributing to the stabilization of the quality of the asphalt mixture.
[0030] 2. Compositions for building and road construction materials The present invention comprises an aggregate, an alkaline additive, and the composition itself.
[0031] The aggregate is not particularly limited and can be crushed stone, sand, stone powder, etc., as appropriate, and aggregates of any particle size range, such as dense-graded or open-graded, can be used without restriction.
[0032] The amount of aggregate added to the building and road construction material composition is preferably 20 to 95% by weight, and more preferably 30 to 80% by weight.
[0033] The alkaline additive is not particularly limited and can be any compound that becomes an alkaline component through the action of a hardening accelerator (e.g., water). It is also possible to use sodium hydroxide or potassium hydroxide, which are commonly used in saponification reactions. Furthermore, from an environmental standpoint, ordinary cement (ordinary Portland cement), which exhibits a lower hydrogen ion concentration (acting in a pH range closer to neutral) than the aforementioned alkaline component through the action of a hardening accelerator, is preferably used among the cements commonly used as civil engineering materials. Examples of ordinary Portland cement include those mainly composed of tricalcium silicate (3CaO·SiO2), dicalcium silicate (2CaO·SiO2), calcium aluminate (3CaO·Al2O3), calcium aluminoferrite (4CaO·Al2O3·Fe2O3), and calcium sulfate (CaSO4·2H2O). This ordinary cement functions as an alkaline additive because it exhibits alkalinity (lower hydrogen ion concentration compared to sodium hydroxide or potassium hydroxide) through the action of a hardening accelerator such as water. Other examples of alkaline additives include sodium ions (Na + ), potassium ions (K + ), magnesium ions (Mg 2+ ), calcium ions (Ca 2+ Aqueous solutions containing metal ions such as ), powders containing metal salts that decompose into the aforementioned ions when water is added, sodium bicarbonate (NaHCO3), potassium bicarbonate (KHCO3), etc. can be used.
[0034] The amount of alkaline additive added to the building and road construction material composition is preferably 5 to 40% by weight, and more preferably 10 to 35% by weight.
[0035] The amount of this composition added is preferably less than 40% by weight, and more preferably 35% by weight or less, of the building and road construction material composition. Adding it within this range is preferable because it allows for a better curing delay effect without affecting the quality of the building and road construction material composition. The lower limit of the amount of this composition added is not particularly limited, but is preferably 5% by weight, and more preferably 10% by weight.
[0036] In addition to the above, the building and road construction material composition of the present invention may also contain release agents, water-reducing agents, reinforcing agents, hardening accelerators, retarders, waterproofing agents, dispersants, specific gravity additives, embrittlement inhibitors, and the like.
[0037] 3. Asphalt mixture composition The asphalt mixture composition of the present invention comprises asphalt, an alkaline additive, and the composition itself.
[0038] Asphalt is not particularly limited, and any known type can be used. Examples of asphalt include petroleum asphalt (straight asphalt, blown asphalt, modified asphalt (polymer-modified asphalt, semi-blown asphalt, hard asphalt)), natural asphalt, etc. Commercially available asphalt, such as ENEOS's Straight Asphalt 60 / 80, can be used.
[0039] The asphalt content in the asphalt mixture composition is preferably 3 to 20% by weight, and more preferably 5 to 10% by weight.
[0040] The amount of this composition added to the asphalt mixture composition is preferably 60% by weight or less, more preferably 50% by weight or less, and even more preferably 40% by weight or less. Adding it within this range allows for a better hardening delay effect without affecting the quality of the asphalt mixture composition. The lower limit of the amount of this composition added is not particularly limited, but is preferably 5% by weight and more preferably 10% by weight.
[0041] As alkaline additives, those listed in the above-mentioned building and road construction material compositions can be suitably used.
[0042] The content of the alkaline additive is preferably 10 to 300% by weight, and more preferably 15 to 50% by weight, relative to the fatty acids (100% by weight) contained in the asphalt mixture composition.
[0043] In addition to the above, binders, viscosity reducers, surfactants, modifiers, antioxidants, ultraviolet absorbers, and the like can be added to the aforementioned asphalt mixture composition.
[0044] The aggregate may be further added to the asphalt mixture composition. The aggregate can be blended in any proportion.
[0045] The asphalt mixture composition of the present invention can be made to exhibit high strength by hardening through a saponification reaction of fatty acids and alkaline components contained in the mixture when water is added as a hardening accelerator.
[0046] 4.Curable composition The present invention relates to a curable composition obtained by adding water to the aforementioned building and road material composition or asphalt mixture composition.
[0047] The curable composition of the present invention contains a specific amount of a fatty acid having 18 carbon atoms and a specific amount of a polyether polyol, and therefore can delay curing before hydration and can start curing quickly after hydration.
[0048] 5. Curing delay method The hardening delay method of the present invention delays the hardening of a building / road material composition or asphalt mixture composition containing the above composition before the addition of water.
[0049] By including the composition of the present invention, the natural hardening (hardening before water addition) of building and road material compositions and asphalt mixture compositions can be delayed. [Examples]
[0050] The present invention will be described more specifically below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0051] (fatty acid) The fatty acids used in the production of the composition of the present invention are as follows. • SINAR-OL (product name, manufactured by SINARMAS CEPSA) • TFA-125 (product name, manufactured by Tsukuno Oleochemicals Co., Ltd.) • TFA-80MS (product name, manufactured by Tsukuno Oleochemicals Co., Ltd.) • TFA-IS4 (product name, manufactured by Tsukuno Oleochemicals Co., Ltd.)
[0052] The composition of the aforementioned fatty acids was analyzed according to ISO standard 12966-1:2014 using the following method. The results are shown in Table 1 below.
[0053] (Methods for analyzing fatty acids) [Gas chromatography (GC) measurement] As a pretreatment for gas chromatography analysis, the mixed fatty acids were methylated using the following method. • Methylation method: 5 mL of a methylation reagent, boron trifluoride methanol complex methanol solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), was added to 0.1 mL of mixed fatty acids and heated in a 100°C sand bath for 30 minutes. 50 mL of saturated saline solution and 3 mL of hexane were added and stirred. The upper hexane solution was removed and obtained as the methylated mixed fatty acid. The gas chromatography of the methylated fatty acids in the mixed fatty acid treated as described above was measured under the following conditions. • Analytical instrument: Shimadzu Corporation GC2014 • Analytical column: Sigma-Aldrich SP-2560 capillary column, length x inner diameter = 100m x 0.25mm • Heating conditions: Hold at 180°C for 45 minutes, then increase the temperature to 220°C at a rate of 10°C / minute and hold for 16 minutes. • Detector: Flame ionization detector (FID) • Injection sample: 1.0 μL (hexane solution)
[0054] [Table 1]
[0055] (Example 1) A composition was obtained by mixing 100g of fatty acid (product name: SINAR-OL, manufactured by SINARMAS CEPSA) with 5g of polyoxyalkylene glycol (Brownon PEG-600, polyethylene glycol, number average molecular weight: 600, manufactured by Aoki Oil & Fat Industry Co., Ltd.).
[0056] (Examples 2-21, Comparative Examples 1-7) The compositions were obtained in the same manner as in Example 1, except that the types and amounts of fatty acids and polyoxyalkylene glycols were changed as shown in Table 2. In Table 2, "-" indicates that the corresponding component was not used (the same applies to subsequent tables).
[0057] The abbreviations for polyether polyols in Table 2 are as follows: • PEG600: Brownon PEG-600 (product name), polyethylene glycol, number average molecular weight: 600, manufactured by Aoki Oil & Fat Industry Co., Ltd. • PP-200: Sannix PP-200 (product name), polypropylene glycol, number average molecular weight: 200, manufactured by Sanyo Chemical Industries, Ltd. • TP-400: Sannix TP-400 (product name), trimethylolpropane-based polyether polyol, number average molecular weight: 400, manufactured by Sanyo Chemical Industries, Ltd. • PE-61: Newport PE-61 (product name), polyoxyethylene polyoxypropylene glycol (EO / PO (molar ratio) = 12.5 / 87.5), number average molecular weight: 2000, manufactured by Sanyo Chemical Industries, Ltd. • PE-71: Newport PE-71 (product name), polyoxyethylene polyoxypropylene glycol (EO / PO (molar ratio) = 9.1 / 90.9), number average molecular weight: 2200, manufactured by Sanyo Chemical Industries, Ltd. • PE-75: Newport PE-75 (product name), polyoxyethylene polyoxypropylene glycol (EO / PO (molar ratio) = 42.9 / 57.1), number average molecular weight: 3500, manufactured by Sanyo Chemical Industries, Ltd.) • P-106: Brownon P-106 (product name), polyoxyethylene polyoxypropylene glycol (EO / PO (molar ratio) = 60 / 40), number average molecular weight: 2500, manufactured by Aoki Oil & Fat Industry Co., Ltd.
[0058] <Rating> The compositions obtained in the examples and comparative examples were evaluated as follows.
[0059] (Natural curing time) Cement (product name: Ordinary Portland Cement, manufactured by Katei Kagaku Kogyo Co., Ltd.) was placed in a glass cup container, and 100 parts by weight of the freshly prepared composition was mixed with 100 parts by weight of the cement, and the mixture was allowed to stand. After standing, every 30 minutes, the natural hardening time was defined as the point at which the mixture no longer fell out when the container was turned upside down for 30 seconds. The evaluation results are shown in Table 2 below. In Table 2, "-" in the polyether polyol column indicates that polyether polyol was not used, and "-" in the natural hardening time column indicates that it was not measured (the same applies to subsequent tables).
[0060] [Table 2]
[0061] Table 2 above shows that adding polyether polyols increases the time to spontaneous hardening before hydration. Furthermore, the results from Comparative Example 1 and Examples 4, 7, 9, 13, and 16 show that a hardening delay effect is achieved even at low concentrations of polyether polyols. Additionally, it was found that the spontaneous hardening time increases with increasing concentration of polyether polyols. Examples 19, 20, and 21 also show that the effect is observed with various fatty acids.
[0062] (Evaluation of heat resistance and thermal stability) The compositions of the examples and comparative examples are placed in glass cups X 1 The composition was weighed in grams and placed in a 160°C dryer (under an air atmosphere) for 24 hours, after which its weight was measured again (X 2 g) The evaporation rate was calculated using the following formula. A lower evaporation rate indicates higher heat resistance and thermal stability. Evaporation rate (%) = (X 1 -X 2 ) / X1 ×100
[0063] [Table 3]
[0064] From Table 3, it was found that Examples 5, 14 and 17 with the addition of polyether polyol had improved heat resistance and thermal stability as compared with Comparative Example 1 without the addition of polyether polyol.
[0065] (Example 22) In a glass cup container, straight asphalt (60 / 80, manufactured by ENEOS, referred to as "StAS" in the table) and a fatty acid (trade name: SINAR-OL, manufactured by SINARMAS CEPSA) were mixed at a weight ratio of 2:1, then to the mixture was added Sannix TP-400 (a trimethylolpropane-based polyether polyol, number average molecular weight: 400, manufactured by Sanyo Chemical Industries, Ltd.) as the polyether polyol, and further cement (trade name: Ordinary Portland Cement, manufactured by Kataguchi Kagaku Kogyo Co., Ltd.) was mixed to obtain an asphalt mixture composition. The polyether polyol was added in an amount of 1 wt% relative to the fatty acid (100 wt%), and the cement was added in an amount of 25 wt% relative to the fatty acid (100 wt%). In addition, the total addition amount of the present composition (that is, the total addition amount of the fatty acid and the polyether polyol) was 31 wt% in the asphalt mixture composition.
[0066] (Examples 23 to 29, Comparative Example 8) An asphalt mixture composition was obtained in the same manner as in Example 22, except that the type and addition amount of the polyoxyalkylene glycol were changed as described in Table 4.
[0067] <Evaluation> The following evaluations were performed using the compositions obtained in the Examples and Comparative Examples.
[0068] (Measurement of natural curing time) The asphalt mixture compositions obtained in Examples 22-29 and Comparative Example 8 were placed in containers and left to stand with a glass rod inserted into them. After standing, the glass rod was lifted every 12 hours, and the point at which the container no longer slid down for 30 seconds was defined as the natural hardening time. The results are shown in Table 4.
[0069] [Table 4]
[0070] (Example 30) In a container, straight asphalt (60 / 80, manufactured by ENEOS, "StAS" in the table) was mixed with fatty acid (product name: SINAR-OL, manufactured by SINARMAS CEPSA) in a weight ratio of 2:1. To this mixture, Sannix TP-400 (trimethylolpropane-based polyether polyol, number average molecular weight: 400, manufactured by Sanyo Chemical Industries, Ltd.) was added as a polyether polyol, and then cement (product name: Ordinary Portland Cement, manufactured by Katei Kagaku Kogyo Co., Ltd.) was added to obtain an asphalt mixture composition. The amount of polyether polyol added was 1% by weight relative to the fatty acid (100% by weight), and the amount of cement added was 25% by weight relative to the fatty acid (100% by weight). The amount of this composition added (i.e., the total amount of fatty acid and polyether polyol added) was 31% by weight of the asphalt mixture composition.
[0071] (Examples 31-33, Comparative Example 9) An asphalt mixture composition was obtained in the same manner as in Example 30, except that the type and concentration of polyoxyalkylene glycol were changed as shown in Table 5.
[0072] <Rating> The compositions obtained in the examples and comparative examples were evaluated as follows.
[0073] (Penetration and curing time after water addition) In Examples 30-33 and Comparative Example 9, water was added to the asphalt mixture compositions obtained by Examples 30-33 and Comparative Example 9 in an amount of 20 parts by weight per 100 parts by weight of cement. After mixing and standing, the time until hardening was measured (hardening time after water addition). Furthermore, the penetration depth was measured 24 hours after hardening. Penetration depth is expressed in units of 1 / 10 mm, according to the Japanese Industrial Standard (JIS k 2207:2006 Petroleum Asphalt), using the penetration amount of a standard needle at 25°C. The results are shown in Table 5.
[0074] [Table 5]
[0075] As is clear from Table 5, the curing time after hydration was the same for Examples 30-33, which had polyether polyol added, and Comparative Example 9, which did not have polyether polyol added. Furthermore, the penetration was also similar. In other words, the addition of polyether polyol did not affect the curing time after hydration and did not affect the handling properties of the asphalt mixture composition. It also did not affect the hardness of the final asphalt.
[0076] (Example 34) A composition was obtained by mixing 100g of fatty acid (product name: SINAR-OL, manufactured by SINARMAS CEPSA) with 1g of polyoxyalkylene glycol (Newpol PE-61, polyoxyethylene polyoxypropylene glycol (EO / PO (molar ratio) = 12.5 / 87.5), number average molecular weight: 2000, manufactured by Sanyo Chemical Industries, Ltd.). A glass cup container was filled with cement (product name: ordinary Portland cement, manufactured by Katei Kagaku Kogyo Co., Ltd.), 100 parts by weight of aggregate (product name: silica sand No. 7, manufactured by Toyo Materan Co., Ltd.) was added to 100 parts by weight of cement, and 100 parts by weight of the composition prepared above was added to 100 parts by weight of cement and mixed to obtain a building and road construction material composition.
[0077] (Example 35, Comparative Example 10) A building and road construction material composition was obtained in the same manner as in Example 34, except that the type and amount of polyoxyalkylene glycol were changed as shown in Table 6.
[0078] <Rating> The compositions obtained in the examples and comparative examples were evaluated as follows.
[0079] (Natural curing time) The construction and road material compositions prepared as described above were left to stand. After standing, curing was completed when the material no longer fell out when the container was inverted for 30 seconds, and this was defined as the natural curing time. The results are shown in Table 6.
[0080] [Table 6]
[0081] As is clear from Table 6, it was found that adding polyether polyols extended the time until the construction and road material compositions were naturally cured before the addition of water.
Claims
1. A composition comprising an acid component and a polyether polyol, The aforementioned acid component contains a fatty acid with 18 carbon atoms in an area ratio of 40% or more of the total acid component as measured by gas chromatography. A composition in which the content of the polyether polyol is less than 20% by weight relative to the acid component.
2. The composition according to claim 1, wherein the acid component is a fatty acid mixture containing two or more fatty acids.
3. The composition according to claim 1, wherein the polyether polyol is a curing retarder.
4. A building and road construction material composition comprising aggregate, an alkaline additive, and the composition described in claim 1.
5. A curable composition obtained by further adding water to the building and road construction material composition described in claim 4.
6. An asphalt mixture composition comprising asphalt, an alkaline additive, and the composition described in claim 1.
7. A curable composition obtained by further adding water to the asphalt mixture composition described in claim 6.
8. A method for delaying the hardening of the building and road material composition described in claim 4 or the asphalt mixture composition described in claim 6 before the addition of water.
Citation Information
Patent Citations
Hot asphalt mixture for normal temperature installation
JP2010248472A